Pedicle Screw Placement Using Augmented Reality Surgical Navigation With Intraoperative 3D Imaging: A First In-Human Prospective Cohort Study. Issue 7 (1st April 2019) - Elmi-Terander, Adrian; Burström, Gustav; Nachabe, Rami; Skulason, Halldor; Pedersen, Kyrre; Fagerlund, Michael; Ståhl, Fredrik; Charalampidis, Anastasios; Söderman, Michael; Holmin, Staffan; Babic, Drazenko; Jenniskens, Inge; et al.
Abstract : Study Design: Prospective observational study. Objective: The aim of this study was to evaluate the accuracy of pedicle screw placement using augmented reality surgical navigation (ARSN) in a clinical trial. Summary of Background Data: Recent cadaveric studies have shown improved accuracy for pedicle screw placement in the thoracic spine using ARSN with intraoperative 3D imaging, without the need for periprocedural x-ray. In this clinical study, we used the same system to place pedicle screws in the thoracic and lumbosacral spine of 20 patients. Methods: The study was performed in a hybrid operating room with an integrated ARSN system encompassing a surgical table, a motorized flat detector C-arm with intraoperative 2D/3D capabilities, integrated optical cameras for augmented reality navigation, and noninvasive patient motion tracking. Three independent reviewers assessed screw placement accuracy using the Gertzbein grading on 3D scans obtained before wound closure. In addition, the navigation time per screw placement was measured. Results: One orthopedic spinal surgeon placed 253 lumbosacral and thoracic pedicle screws on 20 consenting patients scheduled for spinal fixation surgery. An overall accuracy of 94.1% of primarily thoracic pedicle screws was achieved. No screws were deemed severely misplaced (Gertzbein grade 3). Fifteen (5.9%) screws had 2 to 4 mm breach (Gertzbein grade 2), occurring in scoliosis patients only. Thirteen of those 15 screws were larger than the pedicle in which they were placed. Two medial breaches were observed and 13 were lateral. Thirteen of the grade 2 breaches were in the thoracic spine. The average screw placement time was 5.2 ± 4.1 minutes. During the study, no device-related adverse event occurred. Conclusion: ARSN can be clinically used to place thoracic and lumbosacral pedicle screws with high accuracy and with acceptable navigation time. Consequently, the risk for revision surgery and complications could be minimized. Level of Evidence: 3 Abstract : A prospective clinical study for pedicle screw placement with augmented reality surgical navigation including intraoperative 3D imaging in a hybrid operating room was performed in 20 patients of whom 13 had scoliosis. The screw placement accuracy was 94.1% with an average navigation time of 5.4 minutes per screw placement.